Analisis Penanggulangan Resiko Kecelakaan Kerja Proses Sandar Kapal di Pelabuhan Tanjung Perak Surabaya - Fajar Dadang Pambayun,; Maulidiah Rahmawati,; Diyah Purwitasari, (Jurnal Bintang Pendidikan Indonesia, 2024)
The port terminal serves as a place for berthing, storing goods, and loading and unloading, which has the potential to jeopardize work safety. The implementation of Occupational Health and Safety (OHS) protects workers from workplace hazards. However, the lack of awareness of workers at the port in wearing Personal Protective Equipment (PPE) while working in the port area is still a problem. This study aims to identify the risks, impacts and efforts to overcome work accidents in the ship berthing process at Tanjung Perak Port Surabaya. Given the importance of using PPE in doing work at the port, work safety is a crucial aspect that must be considered. Using the HAZOPS (Hazard and Operability Study) method, this study identifies potential hazards and provides mitigation actions needed to reduce the risk of accidents in the ship berthing process. This study used purposive sampling technique with a total of 40 officers in the patrol and enforcement section at the Tanjung Perak Surabaya Syahbandar and Main Port Authority (KSOP) Office. Data collection methods are direct observation, documentation, and questionnaires. The results showed that the main factors causing work accidents were equipment failure, human error, and the environment. The highest percentage of accidents is caused by equipment failure, with 63% at the extreme level and 20% at the high level. Therefore, it is necessary to carry out risk control or risk mitigation in the form of routine maintenance on work tools at the port.